Teaching, Learning, and Collaborating: Voices from Instructional Designers when Preparing Graduate Faculty for Online Instruction - Dr. Mattyna Stephens (Adult Education Research Conference, 2019)
The research sought to explore the experiences of eight instructional designers when preparing graduate faculty for online instruction and design.
Keywords: instructional designer; online instruction; graduate faculty